So You Want to Quit Smoking: Have You Tried a Mobile Phone? - Labonne, Julien; Chase, Robert S. (2012)
Using spatially coded data on mobile phone coverage and panel data from 2100 households in 135 communities of the Philippines, we estimate the impact of mobile phone ownership on tobacco consumption. Purchasing a mobile phone leads to a 17.1% decrease in tobacco consumption per adult over the age of 15.